PCR-BASED NATIONAL BACTERIAL MENINGITIS SURVEILLANCE IN TURKEY YEARS 2006 TO 2009 - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Polymerase chain reaction-based surveillance for bacterial meningitis including 841 children revealed 246 with bacterial DNA in cerebrospinal fluid samples of which 53% were Streptococcus pneumoniae, 19% Neisseria meningitidis, and 16% Haemophilus influenzae type b. The most common S. pneumoniae serotypes/serogroups were 1, 19F, 6A/6B, 23F, 5, 14, 18 and 19A. Among 47 meningococci, 86% were serogroup B, 6% serogroup C, 3% serogroup A, 3% serogroup X and 3% serogroup W.
Keywords: surveillance; bacterial; meningitis; Turkey; STREPTOCOCCUS-PNEUMONIAE; NEISSERIA-MENINGITIDIS; DISEASE; ASSAYS